A Database Built Upon the Medical Event Vector - Gleser, M.; Young, G.; Woods, D. (Methods of Information in Medicine, 1979)
PHAMIS is an automated medical information system designed to provide long-term storage and retrieval of clinical information about Public Health Service patients. The patient database is composed of clinical events stored in compact format as multidimensional vectors in a write-once, read-only file to minimize file maintenance. Clinical observations are recorded as pointers to a large and expandable dictionary, rather than as text, to reduce storage requirements. The database design includes both within-patient-record and between-patient-recorcl indexes to speed data retrieval and facilitate report generation.
Keywords: Automated Medical Information Systems; Database Design; Long-term Data Storage